Pengaruh Work-Life Balance dan Dukungan Organisasi terhadap Kinerja Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening pada PT. Reka Frasa Indonesia - Andri Wijaya T; Piter Tiong; Gunawan, Gunawan; Partono Soemaryo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine and analyze the effect of work-life balance and organizational support on employee performance through job satisfaction as an intervening variable at PT. Reka Frasa Indonesia. A quantitative research approach was employed to achieve the research objectives by involving 121 employees of PT. Reka Frasa Indonesia as the research sample. Data were collected through structured questionnaires and analyzed using path analysis. The results of the direct effect analysis indicate that work-life balance and organizational support have a positive and significant effect on job satisfaction. Furthermore, work-life balance, organizational support, and job satisfaction also have a positive and significant influence on employee performance. The results of the indirect effect analysis reveal that job satisfaction mediates the relationship between work-life balance and organizational support and employee performance. These findings suggest that improving work-life balance and strengthening organizational support can enhance employees’ job satisfaction, which in turn contributes to improved employee performance. Therefore, organizations are encouraged to develop policies and work environments that promote work-life balance and provide adequate organizational support to achieve optimal employee performance at PT. Reka Frasa Indonesia in Makassar.